Increasing the Activity and Skills of Writing Hots Negotiating Text Through Audio-Visual Media - Marti Marganingsih; Aceng Hasani; Erwin Salpa Riansi (Universitas Indraprasta PGRI, 2022)
The author conducted this Classroom Action Research aiming to find the right media as a means of improvement the writing skills of HOTS negotiating texts for SMKN 8 students Tangerang Regency. The data used are qualitative data and quantitative data obtained from preliminary study results, period I, and period II through the learning process St Class X TKJ 4 SMKN 8 Tangerang Regency. The results of the study in the first cycle in the form of HOTS writing texts that described the ability of class X TKJ 4 students in understanding writing negotiating texts. The results in cycle I showed an average value of 77 with an increase of 0.2compared to the results in the pre-cycle. To achieve maximum results, the author conducts a research cycle. The results of research in cycle II were in the form of HOTS writing texts that described students' abilitiesclass X TKJ 4 students in understanding writing negotiating texts. The results in cycle II showed an average value of 93, an increase of 1.6 compared to the results in the pre-cycle.Keywords: Hots writing activeness and skills, negotiation text, audio-visual media